2010
DOI: 10.1007/s00421-010-1756-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immune function after short-term administration of recombinant human growth hormone in healthy young males

Abstract: It is reported that in both elite and recreational athletes Growth Hormone (GH) is the most commonly used drug aimed at improving sport performance. Aim: The purpose of the present study was to evaluate the immunomodulatory effects of short-term administration of recombinant human GH (rhGH) in healthy young males. NK cell number, activity and phenotype, T cell number, cytokine production of IL-2, IL-4, IL-6, IL-10, TNF-α and IFN-γ and CD4 + /CD8 + ratio with particular attention to the possible correlation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Our findings are similar to those demonstrated by Michalacous et al in which GH did not correlate with TNF α in GH deficient children or in short stature children as a group [8]. Ramos et al also failed to identify a relationship between acute GH administration and cytokine production in a population of healthy young men [7].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are similar to those demonstrated by Michalacous et al in which GH did not correlate with TNF α in GH deficient children or in short stature children as a group [8]. Ramos et al also failed to identify a relationship between acute GH administration and cytokine production in a population of healthy young men [7].…”
Section: Discussionsupporting
confidence: 91%
“…To the contrary, other studies conducted in healthy young males as well as post-surgical patients demonstrate no effect of short term GH administration on cytokine secretion [7] [10]. Micahelous et al also revealed no correlation between TNF α and GH levels in GH deficient or idiopathic short stature patients [8].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown both positive and negative results regarding the effects of GH treatment on the haematopoietic system with findings of both increased haematopoiesis 44,45 and enhanced NK cell activity, 16,38,39 as well as unaffected blood cell counts 36,46,47 . As the negative findings are conducted in studies involving healthy subjects, it seems likely that patients with immune depletion have a more pronounced effect of supplementary GH and IGF‐1, while immune function in healthy individuals is largely independent of these hormones 47 …”
Section: Discussionmentioning
confidence: 99%